ANALISIS PERAMALAN PERMINTAAN KARTON BOX UD BERKAH JAYA OFFSET MENGGUNAKAN METODE TIME SERIES - Yoga Satya Andriawan; Nur Muflihah (INVANTRI (Inovasi Dan Pengelolaan Industri), 2023)
UD Berkah Jaya Offset is one of the manufacturing companies operating in the field of cardboard box production. The company offers a variety of cardboard box products in various sizes, including sizes D1, D2, D3, trepes, and roll. In the production of cardboard boxes, particularly size D1, issues such as overstock and even stock shortages have been frequently encountered during the period from January 2022 to December 2023. This is due to the ineffective demand forecasting to anticipate these possibilities. This study aims to forecast the demand for size D1 cardboard boxes for the upcoming months using the best forecasting method. The methods employed are decomposition method, Winter's exponential smoothing, and Holt's exponential smoothing. This research compares the three methods based on the smallest Mean Absolute Percentage Error (MAPE) value. The results of the study reveal that the decomposition method is the most effective, with a MAPE value of 19, MAD value of 28000, and MSD value of 1247419480, indicating a low level of forecasting error compared to the others.